Business plan: Sustainable surf resort in Simeulue - Vuorela, Roni Samuli (2022)
The growing number of surfers is currently driving surf travellers to expand into remote regions with newly discovered surf breaks. Indonesia’s favourable weather system and a vast exposed coastline makes the region one of the worlds surf richest corners, attracting an increasing amount of surf minded visitors. This Business plan describes the development of a sustainable Surf & wellness resort on the island of Simeulue, Indonesia. This innovative concept distinguishes itself from the already existing surf lodgings in Indonesia due to its unique approach on wellbeing, sustainability, and connection with the local communities. The business plan is written based on a literature review, authors first hand research on the island of Simeulue and research on various sources in order to write an adequate and realistic business plan.